Financial literacy and green finance: catalysts for green economic recovery in smes - Kesuma, Muhammad Ramadhani; Irianto, Ellen D. Oktanti; Widaryo, Chandika Mahendra; Henrika, Margareth; Ariswati, Lusiana Desy; Aini, Rohana Nur (Institute of Computer Science (IOCS), 2025)
This study examined the interplay of financial literacy and access to green finance in driving green economic recovery among small and medium enterprises in East Kalimantan, Indonesia, where resource dependence exacerbates environmental vulnerabilities. The core problem addressed was the sluggish adoption of sustainable business practices by these enterprises, hampered by insufficient financial acumen and constrained funding for eco-friendly initiatives. A quantitative survey approach was employed, gathering data from 150 enterprises across agriculture, trade, and services sectors through structured questionnaires. Partial least squares structural equation modeling analyzed the relationships, revealing that financial literacy exerted a strong positive effect on green practice adoption, while green finance access provided both direct and mediated support. Adoption of green practices fully mediated financial literacy's impact on recovery and partially mediated green finance's influence, collectively accounting for over half of the variance in economic and environmental outcomes. These findings underscored the synergistic potential of education and funding in bolstering resilience. Policymakers should prioritize integrated training and streamlined financing to accelerate sustainable transitions, fostering long-term viability in similar contexts.